2014
DOI: 10.1007/s10508-014-0308-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Attraction and Psychological Adjustment in Dutch Adolescents: Coping Style as a Mediator

Abstract: This study examined whether feelings of same-sex attraction (SSA) in 12- to 15-year-old Dutch adolescents were related to psychological health (self-esteem and psychological distress) and whether this relation was mediated by coping styles and moderated by biological sex. Data were collected from 1,546 high school students (802 boys and 744 girls; M age = 13.57 years) by means of standardized measurements. SSA was found to predict lower levels of self-esteem and higher levels of psychological distress. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
1
9
0
2
Order By: Relevance
“…The more frequent consumption of alcohol to cope with personal worries among sexual minority youth compared to heterosexual youth is in line with findings regarding other maladaptive coping styles that have been found to explain psychological health disparities between sexual minority and heterosexual youth (Bos, Van Beusekom, & Sandfort, 2014). Our study also confirms the finding that the mediation effect of drinking to cope with negative emotions on the relationship between discrimination and alcohol-related problems was stronger for lesbian, gay and bisexual students than for heterosexual students (Borell et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…The more frequent consumption of alcohol to cope with personal worries among sexual minority youth compared to heterosexual youth is in line with findings regarding other maladaptive coping styles that have been found to explain psychological health disparities between sexual minority and heterosexual youth (Bos, Van Beusekom, & Sandfort, 2014). Our study also confirms the finding that the mediation effect of drinking to cope with negative emotions on the relationship between discrimination and alcohol-related problems was stronger for lesbian, gay and bisexual students than for heterosexual students (Borell et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, we examined to what extent active, avoidant, and passive coping styles were associated with suicidal ideation and attempts. Based on the previous findings (Benatov et al, 2020;Bos et al, 2014;Budge et al, 2013;Ong & Thompson, 2019;Speckens & Hawton, 2005), we hypothesized active coping to be associated with a lower likelihood of suicidal ideation and attempts, and avoidant coping and passive coping to be associated with a higher likelihood of suicidal ideation and attempts. Last, we explored whether these coping styles moderated the associations between minority stressors and suicidal ideation and attempts.…”
Section: Current Studymentioning
confidence: 99%
“…For example, qualitative research showed that (ethnically diverse) SGM youth might use avoidant coping strategies such as hiding their sexual orientation or gender identity (Goldbach & Gibbs, 2015 ; Kuper et al, 2014 ; van Bergen & Spiegel, 2014 ), or use direct problem‐solving to manage minority stress (van Bergen & Spiegel, 2014 ). In addition, quantitative research demonstrated that avoidant coping (Bos et al, 2014 ; Budge et al, 2013 ), palliative reactions (e.g. seeking distraction), passive reactions (e.g., brooding) (Bos et al, 2014 ), cognitive strategies (e.g., distraction), alternative‐seeking strategies (Toomey et al, 2018 ), emotion‐oriented coping strategies (Grossman et al, 2011 ), and maladaptive coping (e.g., such as self‐destruction and denial) (Lehavot, 2012 ) were all associated with poorer mental health among SGM individuals, including anxiety, psychological distress, and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…LHB-jongeren hebben, bijvoorbeeld, een slechtere relatie met ouders en vrienden (interpersoonlijke factoren) in vergelijking met heteroseksuele jongeren en dit draagt ertoe bij dat zij ook meer psychosociale problemen hebben (Bos, Sandfort, De Bruyn, & Hakvoort, 2008). Ook blijkt dat seksuele minderheden een slechtere emotieregulatie hebben en meer destructieve copingstrategieën rapporteren (intrapersoonlijke kenmerken) dan heteroseksuele jongeren en dat dit dan ook weer samenhangt met de verschillen die we tussen beide groepen vinden in hun welbevinden en gezondheid (Bos, Van Beusekom, & Sandfort, 2014;Hatzenbuehler, McLaughin, & Nolen-Hoeksema, 2008). Dergelijke onderzoeken zijn meer nodig!…”
Section: Psychologisch Mediatiemodelunclassified